P554 Point of Care detection of anti-infliximab antibodies in inflammatory bowel disease patients treated with the biosimilar SB2: performance comparison with ELISA. (25th January 2019) - Atreya, R; Schmitt, H; Fischer, S; Neurath, M F; Rekalde, X; Nagore, D; Ametzazurra, A
Abstract: Background: Promonitor ® Quick ANTI-IFX is the only rapid test available for Point of Care (POC) testing of anti-infliximab (IFX) antibodies. The qualitative test is based on Lateral Flow (LF) technology to detect free antibodies to any IFX in human whole blood (capillary or venous), serum or plasma. Detection of anti-Remicade ® and anti-Inflectra ® (CT-P13) antibodies was previously shown to be equivalent in the capillary (finger prick whole blood) and systemic circulations (regular serum collected by venipuncture for therapeutic drug monitoring (TDM). However, detection of antibodies to Flixabi ® biosimilar (SB2, Biogen) had only been proved by ELISA and data were lacking in a LF format. In this study, we compare the performance of the POC LF test to detect anti-Flixabi antibodies with the standard ELISA technique for TDM in IBD patients treated with Flixabi. Methods: Trough ( n = 202) sera collected at the Erlangen University Hospital (Germany) were analysed, corresponding to 76 IBD patients (46 Crohn's disease, 26 ulcerative colitis and 4 indeterminate colitis) treated with Flixabi only. Samples were frozen for subsequent testing with ELISA (Promonitor ® ANTI-IFX, Progenika, Spain) and with the POC test (Promonitor Quick ® ANTI-IFX, Progenika, Spain). The LF test uses the same format as the bridging ELISA. The POC test (LoD=23 AU/ml) results were read visually at 30 min after adding 15 µl of serum, whereas ELISA (LoD=5 AU/ml) quantitative results were categorised as positive or negative to allow comparisons with the POC test. Results: The rapid test correctly detected anti-Flixabi antibodies and showed an almost perfect agreement with the reference ELISA method. 124 out of 202 samples were tested positive for anti-IFX antibodies with the POC test, whereas 144 samples were positive with the ELISA. Positive and negative per cent agreements between ELISA and the POC test were 86.1% and 100%, respectively. Fourteen (70%) out of the 20 discrepancies found were due to anti-Flixabi antibody concentration below the LoD of the POC test. Positive and negative agreements were 95.4% and 100%, respectively (124 LF-positive and 130 ELISA-positive sera) within the common measurement ranges of both techniques. The remaining 6 discrepancies (positive with ELISA and negative with LF) corresponded to samples of 2 patients who were confirmed as true positives by radioimmunoassay. Conclusions: The strong agreement reported here between the Promonitor ® Quick ANTI-IFX POC LF test and the standard ELISA method reinforces that the rapid test is suitable for TDM of any IFX drug.